Analisis Pengendalian Persediaan Bahan Baku Tahu Home Industri Bapak Taryoto Menggunakan Metode Economic Order Quantity (EOQ) - Ubaeddillah, Saeful; Putri, Hana Silvia Dwi; Fatchan, Muhamad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Raw material inventory control plays a crucial role in ensuring the continuity of production in tofu home industries that depend on the daily availability of soybeans. The tofu home industry owned by Mr. Taryoto still applies a simple inventory system, which may cause cost inefficiencies and the risk of raw material shortages. This study aims to analyze soybean raw material inventory control using the Economic Order Quantity (EOQ) method to determine the optimal order quantity, safety stock, and reorder point. This research employs a quantitative descriptive approach with data collected through observation, interviews, and documentation. The research sample consists of soybean usage and purchasing data over a one-year period. The results show that the optimal order quantity is 300 kg per order with a purchasing frequency of 72 times per year, an average inventory of 150 kg, a safety stock of 20 kg, and a reorder point at an inventory level of 140 kg. The implementation of the EOQ method improves inventory efficiency and supports sustainable production continuity.